Antibacterial Action of Lippia origanoides Essential Oil - Francisco Sérgio da Silva Sousa; Dicla Aline Semedo da Veiga; Bernardina De Paixão Santos; Rafaelle Cavalcanti de Lira; Sávio Benvindo Ferreira (Proceedings)
Bacterial resistance to antibiotics makes infections increasingly difficult to fight. In this context, the antimicrobial capacity of Lippia origanoides proved to be a relevant alternative. The purpose of this review is to evaluate the antibacterial activity of this essential oil against bacterial strains. This is a narrative review of the literature using the following guiding question: “Does Lippia origanoides essential oil have antimicrobial activity against bacterial strains?”. The descriptors “Lippia origanoides” and “Antimicrobial activity” were applied to the PubMed, Virtual Health Library (VHL) and Embase databases. The inclusion criteria were as follows: contain, whether in the title, abstract or body of the text, a relationship with the antibacterial activity of L. origanoides, and the possibility of accessing the full article. A total of 62 articles were found and 19 studies were chosen. A total of 13 bacteria were analyzed in the tests and the Minimum Inhibitory Concentration (MIC) was as follows: Bacillus cereus (0.62 μL/mL), Bacillus subtilis (1.25 μL/mL), Staphylococcus aureus (1.25–60 μL/mL), Chromobacterium violaceum (0.37 μL/mL), Escherichia coli (0.15–60 μL/mL), Pseudomonas aeruginosa (240 μL/mL), Salmonella cholerasuis (30 μL/mL), Salmonella thypimurium (1.25 μL/mL) and Vibrio parahaemolyticus (0.313 μL/mL). In Bifidobacterium breve and Lactobacillus acidophilus, the Minimum Bactericidal Concentration (MBC) was, respectively, 50 μL/mL and 3.135 μL/mL. In Staphylococcus epidermidis and Salmonella enteritidis, there was only MIC50 (concentration to inhibit 50% of the sample), specifically, 0.37–3.0 μL/mL and 0.37 μL/mL. In total, 27.3% of articles evaluated the antibiofilm capacity of L. origanoides, and the inhibition of biofilm formation reached more than 70% in E. coli and S. aureus. Lippia origanoides essential oil revealed antimicrobial activity in all studies. Ultimately, P. aeruginosa proved to be a strain that still requires further experimentation.